Agricultural Technical Maintenance in the Republic of Belarus - V. V. Pavlova (Nauka i Tehnika, 2004)
In the process of market reforms introduction of maintenance system as a body of interrelated means, normative documents and executor of services and works with the purpose to ensure efficient designated machinery application and its serviceable condition within the whole service life period takes rather important significance. In order to provide commodity producers with the required types of service it is necessary to create competitive market of service executors. It is recognized that the dealer′s system is the most efficient one out of a great variety of existing and new structures, forms and methods of technical maintenance organization. The system of technical maintenance in the agroindustrial complex of Belarus should ensure profitable conditions of the production activity to all its participants: machinery manufacturers, their users and commercial agents.